ELECTROPERMEABILIZATION FOR ORGANIC MATERIAL – NUMERICAL MODELING (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Electroporation, also known as electropermeabilization (EP), occurs when a cell's transmembrane potential exceeds a critical threshold under the influence of an electric field, corresponding to a limit value of the electric field intensity. EP depends on the distribution of the electric field, which in turn depends on and, here, determines the material's electrical properties. Some critical electric field strengths act as a “switch” for the EP, which is, to some extent, reversible. This paper aims, through numerical experiments, to unveil the effects of the electric field on the poration of an organic substance (lavender) and the thermal stability of the EP cell. The substance is assumed to be a continuous medium with electric-field-dependent material properties.
Keywords: Electropermeabilization (EP); Electric field; Electric conductivity; Heat transfer; Finite element method (FEM)